Hurricanes and tornadoes in action - Spilsbury, Louise; Spilsbury, Richard, 1963- (New York : Rosen Central, 2009)
Describes what causes hurricanes and tornadoes and provides case studies of significant hurricanes and tornadoes, such as Tangail tornado in Bangladesh in 1996, Hurricane Mitch in Central America in 1996, and Hurricane Katrina in the United States in 2005.
What is a hurricane? -- What is a tornado? -- The fastest winds on earth -- Case study: Tangail tornado, Bangladesh, 1996 -- Case study: Hurricane Mitch, Central America, 1998 -- Case study: Oklahoma twisters, U.S.A., 1999 -- Case study: Tornadoes in the U.K., 2005 -- Case study 5 : Hurricane Katrina, U.S.A. 2005 -- Prediction and preparation.
Includes bibliographical references (p. 47) and index.
7.8
5-8
Keywords: Hurricanes -- Juvenile literature; Tornadoes -- Juvenile literature; Hurricanes; Tornadoes; Hurricanes; Tornadoes; Hurricanes; Tornadoes